Effects of exercise intervention on executive function of middle-aged and elderly people: A systematic review of randomized controlled trials - Zheng, Jian; Su, Xuan; Xu, Chang (Frontiers in Aging Neuroscience, 2022)
Background: Executive function will gradually decline with the increase of age, which will have a negative impact on the quality of life and general health. Exercise intervention can improve executive function and prevent its deterioration, but the evidence from randomized controlled trials is not consistent. Aim: To assess the effect of exercise intervention on executive function of healthy middle-aged and elderly people, and briefly describe its mechanism. Methods: A search was conducted using PubMed, Web of science and EBSCO. The searches were limited to English articles published from January 2010 to December 2022. The information is extracted from searched articles included or excluded based on certain criteria. Results: The search returned 2746 records, of which 11 articles were included in the systematic review, and 8 articles were supplemented according to the references included and related reviews. The results show that different types of exercise intervention have positive effects on the executive function of the middle-aged and elderly people. The intervention prescriptions in most studies are executed in medium to low frequency, medium intensity and medium duration, while only 11% of the studies were followed up. Conclusions: The intervention, which was executed twice a week with 30-60 minutes single intervention time and over 12 weeks total duration, showed a good intervention effect. Exercise intervention is to improve executive function by affecting the activation of brain network and the synthesis of neurotransmitters.